A mechanism for substrate quality control in outer membrane protein assembly - Ashton N. Combs; Anna Konovalova; Thomas J. Silhavy (Proceedings of the National Academy of Sciences, 2026)
The assembly of β-barrel proteins into the outer membrane (OM) of Gram-negative bacteria is catalyzed by the β-barrel assembly machine (Bam) complex, which consists of two essential proteins, the BamA β-barrel and the lipoprotein BamD, and three nonessential lipoproteins BamBCE. While it is well established that BamD serves an essential role in regulating the activity of BamA, the physiological reasons underpinning the need for BamD-mediated regulation of β-barrel assembly are unclear. Here, we demonstrate that BamD-mediated regulation of BamA functions as a mechanism of substrate quality control that ensures the efficient assembly of β-barrel proteins into the OM. Through the use of substrate C-terminal fragments and multiple alleles of bamA and bamD that prevent effective regulation of BamA by BamD, we show that BamD activity is necessary to prevent the accumulation of defective β-barrel substrates on BamA. Notably, these bamAD alleles all confer resistance to the Bam complex inhibitor MRL-494 in a manner that correlates with the degree to which BamD activity is bypassed, suggesting that MRL-494 inhibits β-barrel assembly by disrupting BamD-mediated conformational changes in BamA. We further show that BamD activity functions to prevent the uptake of toxic small molecules across the OM through a mechanism that functionally overlaps with that of the substrate quality control protein Skp. Collectively, these results not only establish that BamD, like Skp, functions to ensure proper quality control of β-barrel substrates but also demonstrate the importance of substrate quality control functions in maintaining the integrity of the OM permeability barrier.